Smart City Kota Magelang : Perubahan Manajemen Pemerintahan Daerah dalam Penerapan Electronic Governance - Yuni Kurniasih; Tri Asih Wismaningtyas (JIAP (Jurnal Ilmu Administrasi Publik), 2020)
Governance perspective appears as a solution to the limitations of the government’s concept. The development of increasingly smart technologies makes the concept of ‘smart’ not only applied to a variety of devices, but also to various systems and orders. So that management changes by linking information technology in government organizations are needed. This effort is considered effective to improve government performance, especially in public services. This research using qualitative methods. This aims of this research is to find out how management changes of the Magelang City as a smart city and to find out whether are all components of both the government environmental and the communities are ready for the existence of smart city. The results of this research are management changes of Magelang City as smart city has begun. That is can be analyzed in the form of framework thinking changes, changing the structure, re-empowerment, and renewal. Readiness of the government of Magelang City is already exist to confront as smart city, but it still needs more improvement. Therefore, in the implementation of smart city program, the government of Magelang City should encourage socialization to the society that there is a form of public service through utilize information technology and carry out deliberations on it to stakeholders in order to create cooperation to realize the actual concept of smart city in Magelang City.